The effects of exercise capacity and sedentary lifestyle on haemostasis among middle-aged women with coronary heart disease - Nagy, Edit; Janszky, Imre; Eriksson-Berg, Margita; Al-Khalili, Faris; Schenck-Gustafsson, Karin (Thrombosis and Haemostasis, 2008)
Previous studies have established a link/relationship between haemostatic factors and increased risk of cardiovascular disease. In addition, physical conditioning is associated with lower coronary heart disease risk. The purpose of this study was to assess the association between physical exercise and haemostatic factors among middle-aged women surviving an acute coronary event. The Stockholm Female Coronary Risk Study included 292 women aged < 65 years, resident in the greater Stockholm area, who were hospitalized for an acute coronary syndrome. Extensive clinical screening including exercise testing, and blood tests were performed 3–6 months after the coronary event. Self-reported physical activity was assessed by a WHO questionnaire. Patients on warfarin treatment were excluded from our analyses. Haemostatic factors were generally higher among physically inactive patients when compared to physically active women in our univariate models. Exercise capacity had a statistically significant relationship with factor VII antigen (p=0.039) and vWFag (p=0.038) even in our multiadjusted analyses. Physical inactivity and poor physical fitness are associated with a potentially prothrombotic blood profile in middle aged women with coronary heart disease.
Keywords: Coagulation; fibrinolysis; exercise capacity; women; coronary artery disease